2013
DOI: 10.1186/1471-2334-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Xpert MTB/RIF and MODS assay for the diagnosis of pediatric tuberculosis

Abstract: BackgroundTuberculosis (TB) in children is rarely confirmed due to the lack of effective diagnostic tools; only 10 to 15% of pediatric TB is smear positive due to paucibacillary samples and the difficulty of obtaining high-quality specimens from children. We evaluate here the accuracy of Xpert MTB/RIF in comparison with the Micoroscopic observation drug susceptibility (MODS) assay for diagnosis of TB in children using samples stored during a previously reported evaluation of the MODS assay.MethodsNinety-six el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 21 publications
5
51
1
1
Order By: Relevance
“…En diferentes estudios realizados en niños, la sensibilidad de Xpert MTB/RIF en EI con baciloscopia positiva varía de 92 a 100% [24][25][26] y cuando se emplean muestras de jugo gástrico, la sensibilidad se estima entre 64 y 95% 8,27,28 . En nuestro caso el único paciente con baciloscopia positiva también presentó resultado positivo de la prueba molecular en EI, con una sensibilidad del 100%.…”
Section: Discussionunclassified
“…En diferentes estudios realizados en niños, la sensibilidad de Xpert MTB/RIF en EI con baciloscopia positiva varía de 92 a 100% [24][25][26] y cuando se emplean muestras de jugo gástrico, la sensibilidad se estima entre 64 y 95% 8,27,28 . En nuestro caso el único paciente con baciloscopia positiva también presentó resultado positivo de la prueba molecular en EI, con una sensibilidad del 100%.…”
Section: Discussionunclassified
“…[50] has concluded that this test will not be a crucial diagnostic tool in high burden countries, the WHO endorsed its use in children in 2013. Several studies published on its use in the pediatric population have shown promising results be it in gastric lavage [51,52], sputum [53][54][55][56][57][58][59], bronchoalveolar lavage specimens [60], or stool in HIV-infected patients [61].…”
Section: Xpert Mtb/rifmentioning
confidence: 98%
“…Liquid methods are based on two characteristics of M. tuberculosis: its faster growth and its distinctive morphology in liquid media. Recently, another liquid culture-based method, known as microscopic observation drug susceptibility (MODS), has been evaluated in three studies done in Vietnam, respectively, on 705, 96 and 73 children, including overall 1524 pediatric samples [62][63][64]. In the first study, MODS sensitivity was compared with Lowenstein-Jensen culture, resulting higher considering both by patients and by samples (46 vs 38.9%; 35.3 vs 30.3%; p < 0.001) [62].…”
Section: Microscopic Observation Drug Susceptibility Assaymentioning
confidence: 99%